BET 1: Give prehospital blood and save a life?. Issue 6 (19th May 2016) - Scott, Nicholas; Sutton, Sarah
Abstract : A short cut review was carried out to establish whether prehospital blood transfusion in the trauma patient with active haemorrhage can reduce mortality. 11 directly relevant papers were found using the reported search strategy. Of these two presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. It is concluded that prehospital blood transfusion may reduce short-term mortality in these patients, but that the evidence level is low and further definitive randomised controlled trials are needed to prove benefit.